2022
DOI: 10.3389/fimmu.2022.907529
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Impact Cellular and Inflammatory Gene Expression and Immune Response

Abstract: Human milk harbors complex carbohydrates, including human milk oligosaccharides (HMOs), the third most abundant component after lactose and lipids. HMOs have been shown to impact intestinal microbiota, modulate the intestinal immune response, and prevent pathogenic bacterial binding by serving as decoy receptors. However, the direct effect of HMOs on intestinal function and immunity remains to be elucidated. To address this knowledge gap, 21-day-old germ-free mice (C57BI/6) were orally gavaged with 15 mg/day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 97 publications
1
6
1
Order By: Relevance
“…Similarly, HMOs supplementation increased ileum villus height in SMM + HMOs and NSM + HMOs groups compared to the MFM group though this effect was not seen when the MFM group was fed with HMOs. In contrast to these findings, in our previous study, villus height was decreased in germ-free mice supplemented with HMOs for 14 days ( 7 ). Since there was an absolute absence of microbiota in that study, the increase in villus height observed in the current study implicates microbiota and HMOs interaction effects.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Similarly, HMOs supplementation increased ileum villus height in SMM + HMOs and NSM + HMOs groups compared to the MFM group though this effect was not seen when the MFM group was fed with HMOs. In contrast to these findings, in our previous study, villus height was decreased in germ-free mice supplemented with HMOs for 14 days ( 7 ). Since there was an absolute absence of microbiota in that study, the increase in villus height observed in the current study implicates microbiota and HMOs interaction effects.…”
Section: Discussioncontrasting
confidence: 99%
“…In germ-free mice, the immune system is not well developed, signifying the importance of microbiota in immune system development ( 51 , 52 ). HMOs can also modulate both innate and adaptive immune cell composition either directly or via modulating microbiota or microbial metabolites ( 5 , 7 , 53 ). In our study, HMOs supplementation elevated CD8+ T cells in the SMM group and Foxp3+ T regulatory cells (Tregs) in the MFM group in the MLN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These direct effects are difficult to distinguish in in vivo models and clinical studies due to the presence of the microbiome. Furthermore, the large structural variety of HMOS makes identifying structure-function relationships from pooled HMOS challenging, although improved immune maturation has been attributed to the total mixture of HMOS present in human milk [41][42][43][44]. Using an established transwell mucosal immune model combining both IEC and activated PBMC coculture and the presence of a bacterial or allergic trigger, differential immunomodulatory properties of specific HMOS have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increased focus on the cellular, molecular, and nutritional composition of HM and on the relationship between HM and the infant gut microbiomeimmune axis. Research has elucidated mechanisms influencing the development of NEC in preterm infants, with HM components such as HM oligosaccharides, [47][48][49][50] exosomes, 51,52 fatty acids and lipids, 53 lactoferrin, 54 immunoglobulins, 54,55 and many other bioactive factors 56 offering tailored protection against NEC and other hospital-associated diseases. Emerging evidence reveals that HM from the infant's own lactating parent (ie, MHM) is associated with epigenetic variation in DNA methylation, 57,58 which may provide protection against oxidative stress that could contribute to NEC.…”
Section: Potential Mechanismsmentioning
confidence: 99%